A Novel Loss-of-Function MKRN3 Variant in a Chinese Patient With Familial Precocious Puberty: A Case Report and Functional Study - Yin, Xueling; Wang, Junqi; Han, Tianting; Tingting, Zhang; Li, Yuhong; Dong, Zhiya; Wang, Wei; Li, Chuanyin; Lu, Wenli (Frontiers in Genetics, 2021)
Background: Central precocious puberty (CPP) is one of the most common and complex problems in clinical pediatric endocrinology practice. Mutation of MKRN3 gene can cause the familial CPP. Methods and Results: Here we reported a Chinese patient bearing a novel MKRN3 mutation (c.G277A/p.Gly93Ser) and showing CPP phenotype. Functional studies found that this mutation of MKRN3 attenuated its autoubiquitination, degradation and inhibition on the transcriptional activity of GNRH1, KISS1 and TAC3 promoter. Conclusion: MKRN3 (Gly93Ser) is a loss-of-function mutation, which attenuated the inhibition on GnRH1 related signaling, suggesting this mutant can lead to central precocious puberty. Key words: Central precocious puberty, MKRN3, ubiquitination,GnRH1